Delayed diagnosis of congenital heart disease worsens preoperative condition and outcome of surgery in neonates. Issue 9 (31st January 2006) - Brown, K L; Ridout, D A; Hoskote, A; Verhulst, L; Ricci, M; Bull, C
Abstract : Objectives: To assess whether the route by which neonatal congenital heart disease (CHD) is first recognised influences outcome after surgery. Methods: Surgical neonates admitted to a tertiary cardiac unit between March 1999 and February 2002 were retrospectively reviewed with analysis of risk factors for outcome. Three routes to initial recognition of CHD were compared: antenatal diagnosis, detection on the postnatal ward, and presentation after discharge to home. Outcome measures were mortality and duration of perioperative ventilation. Results: 286 neonates had cardiac surgery with a median duration of ventilation of 101 h and in-hospital mortality of 12%. Recognition of CHD was antenatal in 20%, on the postnatal ward in 55% and after discharge to home in 25%. Multiple regression analyses, including the cardiac diagnosis, associated problems and other risk factors, indicated that severe cardiovascular compromise on admission to the cardiac unit was significantly related to mortality and prolonged ventilation. Considered in isolation, the route to recognition of heart disease did not influence mortality or ventilation time. Route to initial recognition did, however, influence the patient's condition on admission to the cardiac unit. Cardiovascular compromise and end organ dysfunction were least likely when recognition was antenatal and most common when presentation followed discharge to home. Conclusion: The setting in which neonatal CHD is first recognised has an impact on preoperative condition, which in turn influences postoperative progress and survival after surgery. Optimal screening procedures and access to specialist care will improve outcome for neonates undergoing cardiac surgery.